CAUSES AND INITIAL SYMPTOMS OF DIABETES, PREVENTION AND DIAGNOSIS OF DIABETES, EARLY DETECTION AND TREATMENT OF DIABETES. - Umarov Fakhriddin Bakhriddin oglu (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about diabetes, its causes, changes and complications that occur in the cardiovascular system due to diabetes. In the article, the important factors of the work being done on the prevention and diagnosis of diabetes mellitus, early detection and treatment of diabetes mellitus, which is one of the topical issues of the present day, were explained. The opinions of great doctors about the prevention of diabetes are given. Objective and subjective factors of diabetes are explained. Information is given about the work carried out in Uzbekistan related to the prevention and diagnosis of diabetes, early detection and treatment of diabetes